2020
DOI: 10.3390/catal10030300
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Fingerprint of CuS-Hexagonal Chemistry from (Bis(N-1,4-Phenyl-N-(4-Morpholinedithiocarbamato) Copper(II) Complexes) as Photon Absorber in Quantum-Dot/Dye-Sensitised Solar Cells

Abstract: The main deficit of quantum dot/dye-sensitised solar cells (QDSSCs) remains the absence of a photosensitiser that can absorb the entire visible spectrum and increase electrocatalytic activity by enhancing the conversion efficiency of QDSSCs. This placed great emphasis on the synthesis route adopted for the preparation of the sensitiser. Herein, we report the fabrication of hexagonal copper monosulfide (CuS) nanocrystals, both hexadecylamine (HDA) capped and uncapped, through thermal decomposition by thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…These peaks were related to lattice planes of (100), ( 103), ( 105), ( 106), (008), and (110) as the covellite CuS phase (JCPDS file: 06-0464). [43][44][45] The results were consistent with a selected area electron diffraction (SAED) pattern (103, 105, and 008) (Figure S3). The analysis of EDS confirmed that S and Cu had a coinciding distribution and the molar ratio of S/Cu obtained from quantitative analysis was ~2:3 (Figure 2E).…”
Section: Synthesis and Characterization Of Pccnssupporting
confidence: 83%
“…These peaks were related to lattice planes of (100), ( 103), ( 105), ( 106), (008), and (110) as the covellite CuS phase (JCPDS file: 06-0464). [43][44][45] The results were consistent with a selected area electron diffraction (SAED) pattern (103, 105, and 008) (Figure S3). The analysis of EDS confirmed that S and Cu had a coinciding distribution and the molar ratio of S/Cu obtained from quantitative analysis was ~2:3 (Figure 2E).…”
Section: Synthesis and Characterization Of Pccnssupporting
confidence: 83%
“…MoS 2 exhibited the lowest PCE; this was due to the nanoparticles having a higher charge transfer resistance, which resulted in the limitation of electron transfer, subsequently resulting in low electron–hole recombination, hence, in limited efficiency [ 22 ]. Low efficiency might be due to the increased surface area and thickness on the photoanode which results in charge transfer resistance [ 23 , 24 ]. Furthermore, according to the chemical composition of the samples, the fill factor (FF) was used to determine the quality of the fabricated QDSSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis procedure for ligands and complexes conducted in this work was adopted and modified from the literature and the experiments conducted by Mbese et al, Agoro et al, Meyer et al [ 24 , 25 , 26 ], as well as Halimehjane [ 27 ]. As an example, to explain the synthesis process, the procedure utilized to synthesize MoS 2 was explained.…”
Section: Methodsmentioning
confidence: 99%
“…A single-source method produces high-purity and cost-effective materials by incorporating the required elements into one compound [ 1 , 2 , 3 ]. This approach involves a simple decomposition of the molecular precursor, usually dithiocarbamate metal complexes, in an inert environment to the desired temperature [ 19 , 20 , 21 ]. Such approaches have been employed for the formation of metal oxides and metal chalcogenides with various morphologies for different nanomaterials, such as nanofabrics, nanodiscs, nanorods, nanospheres and nanowires [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%